A comparative analysis of the law and practice relating to refugee protection in Tanzania and South Africa - Rugeiyamu, Juliet Kokutensa (Centre for Law and Society, 2026)
The 20th Century has accurately been described as the century for refugees 1 . Africa today, is one of the biggest producers of refugees in the World. According to UNHCR, there are nearly seven million refugees in Africa, out of a world-wide total of fifteen million. There are, additionally, more than two million displaced persons out of a total of approximately five million persons. In terms of percentage therefore, Africa hosts more than 45% of the World's Refugees and more than 35% of the World's displaced people2 . In 1997, of the ten largest refugee producing countries in the world, seven of them were located in Africa. These countries were Somalia, Rwanda, Burundi, Sudan, Sierra Leone and Eritrea. Africa has, more recently, also witnessed a large increase in the number of refugees being churned out from the Democratic Republic of Congo as a result of it's current internal conflict. All the aforementioned countries have produced mass movements of people seeking protection. Such mass movements have had significant impacts on a number of African nations, including Tanzania and South Africa.